Pattern of Drug Resistance Among “Previously Treated Pulmonary Tuberculosis Cases” Attending Gulab Devi Hospital Lahore - ABDUR RAHMAN, AAMIR RAHIM ZAIB.UN.NISA, ATIQA AMBREEN (Journal of Fatima Jinnah Medical University, 2018)
Objective: To assess the prevalence of drug resistance in previously treated tuberculosis patients attending Gulab Devi Chest Hospital Lahore in 2007. Materials and Methods: Drug susceptibility for first line anti-tuberculosis drugs was done for 214 previously treated pulmonary tuberculosis patients attending Gulab Devi Hospital Lahore. Study period was one year (Jan 2007 – Dec 2007), done by conventional culturing on solid medium (Lowenstein-Jensen medium). Drug sensitivity was applied using the proportion method. Results: A total of 214 isolates of Mycobacterium tuberculosis were obtained from treated patients of pulmonary tuberculosis. All of these patients had taken at least one month or more of first line anti tuberculosis drugs. 120 (56%) were male and 94 (44%) were female. Age distribution was 11-90yrs. 69 patients (32 %) had taken regular treatment while 145 patients (68 %) were having irreguler treatment history. Out of 214 Mycobacterium tuberculosis isolates 78 (36.4 %) were resistant to both isoniazid and rifampicin (multi drug resistance). Overall resistance to isoniazid was observed in 99 patients (46.2%), to rifampicin in 125 patients (58.4%), streptomycin in 100 (46.7%) and to ethambutol in 40 patients(18.6%). Conclusion: In this study, we found a high proportion of multi drug resistance (MDR) in addition to resistance to two or more drugs. This study also underlines the importance of continuous monitoring of trends in drug resistance, which would provide useful input for shaping future policies to prevent the emergence and dissemination of MDR tuberculosis.